Wykorzystanie metod wielowymiarowej analizy danych spektralnych do identyfikacji i klasyfikacji polskich miodów - Jadamus-Hacura, Maria; Hacura, Andrzej (The Application of Multivariate Analysis of Spectra Data in the Identification and Classification of Polish Honeys, 2009)
Infrared Fourier transform spectroscopy with attenuated total reflection (ATR) sampling and multivariate analysis were used for the identification and classification of Polish honey. This method is rapid, non-destructive, with high precision and reliable detection. The 50 honey samples of multifloral and unifloral from different floral sources were precisely measured in mid-infrared region and analyzed with the use of principal component (PCA) and discriminant analysis. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 469-476